Bright Monolayer Tungsten Disulfide via Exciton and Trion Chemical Modulations - Tao, Ye (2018)
Atomically thin transition metal dichalcogenides (TMDCs) with exceptional electrical and optical properties have drawn tremendous attention for novel optoelectronic applications such as photodetectors, transistors and light emitters, etc. However, the electron bound trions formed through the combination of neutral exciton and electron significantly decrease the photoluminescence (PL) efficiency of TMDCs. In this study, we report a simple yet efficient chemical doping strategy to modulate the optical properties of monolayer tungsten disulfide (WS2). As a demonstrative example, the chemical doped monolayer WS2 exhibits remarkably PL enhancement, which is about one order of magnitude higher than pristine WS2. This outstanding PL enhancement is attributed to the fact that the excess electron which promotes the formation of electron bound trions is effectively decreased through charge transfer from WS2 to chemical dopant. Furthermore, an improved degree of circular polarization from ~9.0% to ~41.5% is also observed in the chemical doped monolayer WS2. Our work illustrates a feasible strategy to manipulate optical properties of TMDCs via exciton modulation, making TMDCs promising candidates for versatile semiconductor-based photonic devices.